Strategi Desa Adat Tegenungan Dalam Mengelola Objek Wisata Air Terjun Tegenungan Kecamatan Sukawati Kabupaten Gianyar - Darma Putra, I Gede Arya; Yudartha, Putu Dharmanu; Winaya, I Ketut (CITIZEN CHARTER, 2019)
zABSTRACTz Tegenungan Traditional Village as one of the traditional villages in Gianyar Regency has tourism potential. The unique thing about this Tegenunan Customary Village is that it has been able to manage tourism potential to be developed into an Indigenous Village Owned Enterprise (CV Tegenungan Mertha Jiwa Wahana Tirta). The purpose of this study was to determine extent of the strategy set by Tegenungan Customary Village in managing the attraction of Tegenungan Waterfall. The unit of analysis of this research is the Tegenungan Traditional Village. This research uses explorative qualitative methods. The results of this study indicate that in the implementation of the strategies set by the Tegenungan Customary Village still experiencing some obstacles, obstacles in the field of planning and implementation in the field. This research resulted in a strategy to improve access to tourism objects, improve parking lots, develop tourist attractions owned by the Tegenungan Traditional Village. Keywords:Strategy, Management,Tegenungan Waterfall